The impact of quality assurance systems on the operational performance of laboratories - Ratsoeu, Ellen (2013)
M.Tech. (Operations Management) === It has become a trend for organisations to implement and certify quality systems. The most common quality system that organisations currently implement is ISO 9001. Certification to ISO 9001 has in recent times been used as a marketing tool to enter new markets. Nowadays, customers expect their suppliers and potential suppliers to be certified to ISO 9001. It has become a primary requirement for doing business, and customers now demand it. There have been various studies conducted to establish the advantages of ISO 9001 and its impact on organisational performance. Laboratories are no exception to this developing trend. They are implementing laboratory quality standards like ISO 17025 and the Organisation for Economic Cooperation and Development Good Laboratory Practice (OECD GLP). Some laboratories are now applying for certification of compliance to laboratory standards. Implementing and certifying laboratory systems is an exercise that comes at a cost. The exercise is demanding in terms of human resources, time and capital. There has not been a study conducted to evaluate the impact of these systems on the operational performance of laboratories. This is the reason that resulted in identification of the need to conduct the study. A qualitative research approach was pursued in conducting the study, where the researcher investigated the impact of laboratory quality standards on the operational performance of commercial and non-commercial laboratories. Operational performance in this study is defined as health and safety; supplier selection and performance; human resources; customer satisfaction and profitability. Data was collected through interviews, and was then summarised, and analysed in order to address the research problem. Based on the data collected, it was concluded there is no notable difference in the performance of laboratories with or without quality assurance systems such as ISO 17025 and OECD GLP.